Immune checkpoint inhibitors as mediators for immunosuppression by cancer-associated fibroblasts: A comprehensive review - Eskandari-Malayeri, Fatemeh; Rezaei, Marzieh (Frontiers in Immunology, 2022)
The tumor microenvironment (TME) is a significant contributor to cancer progression containing complex connections between cellular and chemical components and provides a suitable substrate for tumor growth and development. Growing evidence shows targeting tumor cells while ignoring the surrounding TME is not effective enough to overcome the cancer disease. Fibroblasts are essential sentinels of the stroma that due to certain conditions in TME, such as oxidative stress and local hypoxia, become activated, and play the prominent role in the physical support of tumor cells and the enhancement of tumorigenesis. Activated fibroblasts in TME, defined as cancer-associated fibroblasts (CAFs), play a crucial role in regulating the biological behavior of tumors, such as tumor metastasis and drug resistance. CAFs are highly heterogeneous populations that have different origins and, in addition to their role in supporting stromal cells, have multiple immunosuppressive functions via a membrane and secretory patterns. The secretion of different cytokines/chemokines, interactions that mediate the recruitment of regulatory immune cells and the reprogramming of an immunosuppressive function in immature myeloid cells are just a few examples of how CAFs contribute to the immune escape of tumors through various direct and indirect mechanisms on specific immune cell populations. Moreover, CAFs directly abolish the role of cytotoxic lymphocytes. The activation and overexpression of inhibitory immune checkpoints (iICPs) or their ligands in TME compartments are one of the main regulatory mechanisms that inactivate tumor-infiltrating lymphocytes in cancer lesions. CAFs are also essential players in the induction or expression of iICPs and the suppression of immune response in TME. Based on available studies, CAF subsets could modulate immune cell function in TME through iICPs in two ways; direct expression of iICPs by activated CAFs and indirect induction by production soluble and then upregulation of iICPs in TME. With a focus on CAFs' direct and indirect roles in the induction of iICPs in TME as well as their use in immunotherapy and diagnostics, we present the evolving understanding of the immunosuppressive mechanism of CAFs in TME in this review. Understanding the complete picture of CAFs will help develop new strategies to improve precision cancer therapy.